CONFIRMING THE IDENTITY OF THE CIA-CIA LAPORO COMMUNITY THROUGH LOCAL LANGUAGES ON BUTON ISLAND SOUTHEAST SULAWESI - Hasrinando Saputra Laronga; Citra Dewi; Hapsa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
Language is present as a medium to understand each other. However, for the Cia-Cia Laporo community, language is not only a means of communication but also as a medium to gain strength in asserting ethnic identity and as citizens of Laporo descent. This essay aims to describe and to know the position of language as a form of Cia-Cia Laporo's identity. Awareness of the importance of the regional language is then applied in daily life through formal learning methods in schools as well as various traditions and rituals such as sindighao.